Pendekatan Manajemen Strategi Berbasis Perspektif terhadap Pengembangan Jiwa Wirausaha Bagi Pelaku UMKM dalam Mengelola Potensi Usaha Kuliner di Kabupaten Sampang - Hanum , Nindya; Irawati, Anugrahini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Usaha Mikro Kecil, dan Menengah (UMKM) are the pillars of the economy in Indonesia, especially for the people of Sampang Regency. According to Law No. 20 of 2008, Usaha Mikro Kecil, dan Menengah (UMKM) are business activities that are able to increase employment opportunities and provide broad economic services to the community, in addition, they can assist in the process of equitable distribution and increase in community income, encourage economic growth, and maintain national stability. The purpose of this study is to determine the Perspective-based Strategy Management Approach to the Development of the Entrepreneurial Spirit of UMKM Actors in Managing Culinary Business Potential in Sampang District. This research uses a descriptive qualitative method by observing UMKM actors in Sampang Culinary District. The results show that UMKM players already have an entrepreneurial spirit in managing culinary business potential in Sampang District. However, in some aspects, it is still necessary to develop the entrepreneurial spirit.